A Study to Assess the Experience of Nursing Supervisors and Students about Objective Structured Clinical Examination as New Method of Clinical Teaching in Selected Hospital of Metropolitan City - Kshirsagar, Shweta Saisagar (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The study assess the experience of nursing supervisors and students about Objective Structured Clinical Examination (OSCE) as new method of clinical teaching in selected hospital of Metropolitan city. Materials and Methods: A qualitative descriptive research design was adopted for the study. With the help of purposive convenient sampling technique 30 students of RGNM nursing students and nursing supervisors conducting OSCE were enrolled in the study. Setting of the study was MCH laboratory of selected nursing college. Data were analyzed using descriptive and inferential statistics. Results: The findings of the study stated that majority of the respondents 80% belonged to age group of 18–20 years, whereas in gender about 86.66% were male, while 80% belonged to science stream and 100% respondents had previous knowledge of OSCE. Similarly, majority of the respondents agreed to students perception about OSCE were 96.66% and OSCE compared based on frequency and percentage was found excellent 76.66% and respondents stated RCE as good were 56.66% while, 75% of subjects have agreed for OSCE and RCE. Conclusion: The student were found to not have adequate knowledge about OSCE whereas, the supervisor find it easy to evaluate according to the checklist that describe each point and marks, this helped to provide feedback immediately. The student appreciated the marks as there was no bias in their evaluation. Hence, on the basis of all findings it was concluded that OSCE was effective than routine clinical evaluation and student perceived it optimistically.